Hybrid Poly(aryl ether sulfone amide)s for Advanced Thermoplastic Composites. Issue 22 (28th August 2014) - Gardea, Frank; Garcia, Jeannette M.; Boday, Dylan J.; Bajjuri, Krishna M.; Naraghi, Mohammad; Hedrick, James L.; Meier, Michael; Dove, Andrew
<x xml:space="preserve">Abstract</x> An organocatalytic approach to the depolymerization of poly(ethylene terephthalate) (PET) with selected nucleophiles generates high‐value terephthalate‐based monomers. These monomers are subjected to nucleophilic aromatic substitution (SNAr) polymerizations in order to circumvent many of the traditional drawbacks of unmodified materials such as poly(aryl ether sulfone)s (PESs). The synthesis and molecular characterization of novel poly(aryl ether sulfone‐amide)s (PAESAs) containing 10–30 wt% amide functionality are described. PAESAs containing 30 wt% amide are fabricated via extrusion and solvent casting for mechanical characterization. The mechanical behavior of the extruded PAESA is studied through dynamic mechanical analysis (DMA) and tension tests. The DMA studies are performed at a frequency of 1 Hz, in the temperature range of 22–275 °C, indicating a storage modulus of 2.77 ± 0.58 MPa at 30 °C. The glass transition temperature (Tg) of the material, as the temperature corresponding to tanδ peak, is measured to be 217.1 ± 1.7 °C, consistent with DSC measurements. The tension tests on extruded samples reveal a ductile fracture, evidenced with neck formation and propagation on the macroscale, and a rough fracture surface on the microscale. The yield strength of the sample is found to be 52.8 ± 9.2 MPa, with a ductility ranging from 6% to 11%. In contrast to extruded samples, the solvent‐cast PAESA samples fail in a brittle fashion, with relatively smooth fracture surface and no sign of necking. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>